Perubahan Sosial Ekonomi Masyarakat Surulangun Pasca Menjadi ibukota Onder Adeling Rawas Tahun 1901-1942 - Agus Susilo; Sarkowi Sarkowi (Universitas Negeri Padang, 2019)
The event of the conquest of the Palembang Sultanate from the Dutch Colonial nation became a major event. As a large Islamic Sultanate in the archipelago until finally after going through several phases of war must be subdued and accept the defeat agreement from the Netherlands. After mastering the Palembang Darussalam Sultanate, the Dutch Colonial government changed the order of the Sultanate's administration into an Palembang Residency. Of course the status change also affects the area below. This was done by the Dutch colonial government in an effort to regulate a democratic government system in order to support its policies. The Surulangun Rawas area is an area that previously belonged to the Palembang Sultanate, but after coming to power the Dutch Colonial government raised the status of Surulangun Rawas to become the capital of Onder Adeling Rawas. Surulangun became the capital of Onder Adeling Rawas making this area more lively and crowded, because it became the center of the Dutch Colonial government. In the social environment there are many newcomers to this area, not only the Colonial community, but also residents from other regions outside the Surulangun Rawas area. Then pluralism appears in this region. From an economic standpoint, after Surulangun became the capital of Onder Afdeling Rawas, many people were introduced to various new agricultural systems. Many new plants such as rubber, oil palm began to be planted by the people of Surulangun as supporting the export life of the Dutch Colonial government. In the trading system it was also more alive, where the Rawas river was traversed and visited by traders from various regions around Rawas and beyond Rawas.